Effect of Impletol injection into paratonsillar tissue on abnormal sensation in the throat - Yamagiwa, M; Kubo, M; Sakakura, Y (Nippon Jibi Inkoka Gakkai Kaiho, 1989)
If the abnormal sensation, such as a lump or choking, in the throat was mainly caused by inflammatory changes in the palatine tonsils or their surrounding tissues and conveyed via vagal nerve branches distributing there, the sensation might be reduced by topically injected Impletol (Procaine and caffeine in saline solution), i.e. Impletol test for focal tonsillitis. One hundred patients with abnormal sensation in the throat were injected Impletol (Impletol group), 50 patients were injected saline solution alone (Saline group) and 50 patients had injection needle simply inserted into the peritonsillar tissues (Needle group). The Impletol group showed the best result and was followed by Saline group and then Needle group. Namely, the degree of sensation reduced by 80% or more in 38% of the Impletol group and by 50% or more in 62% of them. Those rates were 26% and 60% for Saline group and 28% and 52% for Needle group, respectively. Though the results were indicative of the effectiveness of the Impletol injection for the abnormal sensation in the throat, the difference among these three groups was not statistically significant.